Strengthening the Competitiveness of Indonesian MSMEs in the Malaysian Market - Muhammad Sholahuddin; Nurizal Ismail; Ratna Yunita Setiyani Subardjo; Suranto Suranto; Moechammad Nasir; Mohamad Nisman Fadhil; Muhammad Amir Anshori; Tazkia Amalia; Muhammad Fathi Salim (MALLOMO: Journal of Community Service, 2026)
This community engagement programme aimed to strengthen the competitiveness of Indonesian micro, small and medium-sized enterprises in the Malaysian market through practical entrepreneurship training for Indonesian citizens in Kuala Lumpur and its surrounding areas. The programme was implemented at Rumah Hamka Malaysia and involved 30 existing and prospective entrepreneurs from various business sectors. Using a participatory training approach, the activities focused on target market identification, product attractiveness, business integrity, packaging improvement, and cost-effective promotional strategies. Evaluation was conducted through pre-test and post-test assessments, observation, worksheets, participant feedback, and satisfaction questionnaires. The data were analysed using descriptive analysis and a paired-samples t-test. The results showed a statistically significant improvement in participants’ understanding after the programme. Participants became more capable of identifying market segments, formulating product value, building customer trust, improving packaging presentation, and designing simple promotional messages. This programme concludes that community-based practical training can support Indonesian diaspora entrepreneurs and strengthen the competitiveness of Indonesian micro, small and medium-sized enterprises in Malaysia.